Clinical and pathologic prognostic factors in adult granulosa cell tumors of the ovary. Issue 5 (1st August 2008) - Ranganath, R.; Sridevi, V.; Shirley, S. S.; Shantha, V.
Abstract : The objective of this study was to determine the clinicopathologic prognostic factors in adult granulosa cell tumors of the ovary. A retrospective review of the records of patients of granulosa tumors who were treated at our institute over a period of 10 years (1995–2005) was done. Clinical, pathologic, and follow-up data were collected. A total of 34 patients who were treated during this period were subjected to analysis. Cox univariate analysis and Wilcoxon's test for multivariate analysis were used as part of the SPSS software for examining the data. It was found that optimal cytoreduction ( P = 0.02), presence of nuclear atypia ( P < 0.001), and increased mitoses ( P = 0.03) were the three factors that impacted significantly on survival. Age, stage of the tumor, parity, and size of the tumor had no significant effect on survival. Patients who received chemotherapy had a better median disease-free survival than those who did not (60 vs 48 months), but this did not reach statistical significance ( P = 0.08). Optimal cytoreduction, nuclear atypia, and increased mitoses are the statistically significant prognostic factors and may be used for selecting patients for adjuvant therapy.